A Proteoglycan-Like Molecule Offers Insights Into Ground Substance Changes During Holothurian Intestinal Regeneration. (June 2016) - Vázquez-Vélez, Gabriel E.; Rodríguez-Molina, José F.; Quiñones-Frías, Mónica C.; Pagán, María; García-Arrarás, José E.
Extracellular matrix remodeling is an essential component of regenerative processes in metazoans. Among these animals, holothurians (sea cucumbers) are distinguished by their great regenerative capacities. We have previously shown that fibrous collagen as well as other fibrous components disappear from the connective tissue (CT) early during intestinal regeneration, and later return as the organ primordia form. We now report on changes of the nonfibrous component of the CT. We have used Alcian Blue staining and an antibody, Proteoglycan Like-1 (PGL-1), that recognizes a proteoglycan-like antigen to identify the presence of proteoglycans in normal and regenerating intestines. Our results show that early in regeneration, the ground substance resembles that of the mesentery, the structure from where the new intestine originates. As regeneration proceeds, Alcian Blue staining and PGL-1 labeling reorganize, so that by 4 weeks the normal intestinal CT pattern is achieved. Together with our previous findings, the data suggest that CT components that might be detrimental to regeneration disappear early on, while those that might be beneficial to regeneration, such as proteoglycans, are present throughout the regenerative process.